Construction industry Payment and Adjudication Act 2012: a legal review / Mohammad Afiq Abdul Rahim … [et al.] - Abdul Rahim, Mohammad Afiq; Mohd Shaari, Nurfatin Amirah; Shariffudin, Siti Noor Fatin Aidillah; W. Mustappa, W. Nur Izaty; Mohd Zanib, Zetty Sufina (2014)
This paper is about payment on construction industry in Malaysia. This paper is mainly focusing on the cash flow problem in the Malaysian construction industry where there is delay and non-payment to the subcontractor. Prior 2012, there is no specific Act that statutorily governs the disputes of payment in the construction industry. In this paper, the parties concerned such as the employer, main contractor and the subcontractor will be highlighted. Besides that, this paper will further examine the mode of payment in which from those mechanisms, the disputes of payment had arisen. Not only that, the cash flow problem and the factors that led to it can be seen in this paper. Hence, this paper will concentrate on the newly-enacted Construction Industry Payment and Adjudication Act 2012. This Act is enacted to facilitate regular and timely payment and to provide remedies for the recovery of payment in the construction industry. This paper is set out to see the effectiveness of this newlyenacted Act in solving the disputes of payment to the subcontractor. Finally, an analysis will be made as to see whether the problem of delay and nonpayment to the subcontractor can be solved in pursuance of the provisions provided in the Construction Industry Payment and Adjudication Act 2012. This paper will also provide some possible recommendations in order to lessen the problem of delay and non-payment to the subcontractor.